Conformational properties of DNA containing (CCA)n and (TGG)n trinucleotide repeats - Zemánek, Michal; Kypr, Jaroslav; Vorlícková, Michaela (International journal of biological macromolecules, 2005)
We have used CD spectroscopy, polyacrylamide gel electrophoresis, and UV absorption spectroscopy to study conformational properties of DNA fragments containing (CCA)n and (TGG)n repeats, which are the most length-polymorphic microsatellite sequences of the human genome. The (CCA)n fragments are random single strands at neutral and alkaline pH but they fold into intramolecular intercalated cytosine tetraplexes at mildly acid pH values. More acid values stabilize intermolecular tetraplex formation. The behavior of (TGG)n repeats is more complex. They form hairpins or antiparallel homoduplexes in low salt solutions which, however, are transformed into parallel-stranded guanine tetraplexes at physiological KCl concentrations. Their molecularity depends on the repeat number: (TGG)4 associates into an octameric complex, (TGG)8 forms tetramolecular complexes. (TGG)n with odd repeat numbers (5, 7, and 9) generate bimolecular and tetramolecular tetraplexes. The only (TGG)7 folds into an intramolecular tetraplex at low KCl concentrations, which is antiparallel-stranded. Moreover, the (TGG)(n) fragments provide various mutually slipped conformers whose population increases with salt concentration and with the increasing repeat number. However, the self-structures of both strands disappear in the presence of the complementary strand because both (TGG)n and (CCA)n prefer to associate into the classical heteroduplex. We suppose that the extreme conformational variability of the DNA strands stands behind the length polymorphism which the (CCA)n/(TGG)n repeats exhibit in the human genome.
Keywords: elektroforéza v polyakrylamidovém gelu; konformace nukleové kyseliny; genom lidský; soli; trinukleotidové repetice; cytosin; cirkulární dichroismus; Nucleic Acid Conformation; ultrafialové záření; Nucleic Acid Denaturation; Spectrophotometry; DNA; lidé; mikrosatelitní repetice; denaturace nukleových kyselin; koncentrace vodíkových iontů; chlorid draselný; Genome, Human; Microsatellite Repeats; polymorfismus genetický; Edetic Acid; Oligonucleotides; Trinucleotide Repeats; EDTA; Polymorphism, Genetic; Electrophoresis, Polyacrylamide Gel; Protein Conformation; Humans; Hydrogen-Ion Concentration; Circular Dichroism; Temperature; Salts; spektrofotometrie; Cytosine; Ultraviolet Rays; Potassium Chloride; oligonukleotidy; teplota; konformace proteinů